O ANÁLOGO TRIAZÓLICO DA GRANDISINA PREVINE O PREJUÍZO DE MEMÓRIA ATRAVÉS DE EFEITOS ANTI-INFLAMATÓRIOS E ANTIOXIDANTES EM UM MODELO DA DOENÇA DE ALZHEIMER - ERICK YUDI MARUYAMA RODRIGUES (2023)
Background and Purpose: Alzheimer’s disease is a chronic neurodegenerative disease caused by accumulation of amyloid-beta protein in cortex and hippocampus, leading to neurocognitive impairment due to neuroinflammation and oxidative stress. Current drugs for its treatment are scarce, have explicit side effects and limited efficacy over the disease progression. In this study, we evaluate the effects of a triazole grandisin analogue (TGA) in inflammatory biomarkers and object recognition memory in mice under intracerebroventricular Aβ1-42 injection. Experimental Approach: Male C57/Bl6 mice underwent stereotaxic surgery, receiving intracerebroventricular injections of Aβ or vehicle. Intraperitoneal treatment with TGA (1 mg/kg) or vehicle was repeated for 14 days. One day after the end of treatment, novel object recognition task (NORT) was performed for memory improvement or deficit evaluation. Another set of animals had memantine (10 mg/kg) administered as a positive control for 14 days after Aβ injection, with NORT performed on days 7 and 14 of treatment. At the end of the task animals were euthanized and their cortex and hippocampus underwent oxidative stress and inflammatory biomarkers measurement. Key Results: TGA reduced cortex/hippocampus lipoperoxidation in Aβ1-42 mice, prevented Aβ1-42 cognitive impairment as well as reducing tumor necrosis factor (TNF) and interferon (INF) levels without impacting control group after 14 days of treatment. Memantine failed to prevent lipid oxidation, recognition memory decline and to reduce TNF-INF concentrations. Conclusion and Implications: Such results show that TGA was able to prevent memory impairment due to Aβ injection by antioxidant and anti-inflammatory effects. Moreover, the experimental drug could induce persistent neuroprotective effects, especially compared to memantine, reflecting its innovative properties. Keywords: Alzheimer’s Disease, neolignans, neuroprotection, oxidative stress.